Spent Mushroom Substate (SMS) Usability as Casing Material in Agaricus bisporus Cultivation - Namık Kemal Yücel (Turkish Journal of Agriculture: Food Science and Technology)
In this research, the usability of spent mushroom compost/substrate (SMC/SMS) as casing material was investigated. For this purpose, different volumes of peat and spent mushroom substrate (peat, peat + SMS (1/1), peat + SMS (1/2), peat + SMS (2/1), SMS) were used as casing material. The effects of spent mushroom substrate waste used as casing material and different volumes of peat applications on cap length, cap diameter, stipe length, stipe diameter, hardness, number of mushrooms, average mushroom weight, yield of cultivated mushrooms were determined. Different casing material applications affected stipe length, hardness, number of mushrooms, average mushroom weight and yield. Although the highest yield was obtained from peat application (59.86 kg 100 kg-1 compost), it has been shown that spent mushroom substrate waste can be used in casing material mixtures in mushroom cultivation.